Respuestas

2013-10-10T15:05:45+02:00

Usando propiedades de potencias, la ecuación puede ser escrita:

 2^{x+1} . 2^{3(2x-3)}= 2^{6} = 2^{(x+1)+3(2x-3)}  = 2^{6}

De aqui tenemos:
                             (x + 1) + 3(2x - 3) = 6
                             x + 1 + 6x - 9 = 6
                                     7x = 6 + 9 -1
                                     7x = 14
                                       x = 14/7
                                                      x = 2  RESULTADO FINAL